Synthesis and photophysics of 6-dimethylaminopurine-capped Q-CdS nanoparticles—a study of its photocatalytic behavior - Anil Kumar; Shipra Mital (International Journal of Photoenergy)
Nanoparticles of CdS have been stabilized in aqueous medium by surface capping with 6- dimethylaminopurine at pH 11.0 in the presence of excess Cd2+. The nucleation of the cluster is controlled through coordination of 6-dimethylaminopurine via. -N(CH3)2 group. Excess 6-dimethylaminopurine binds to the core structure through H-bonding involving protonated N(9). CdS capped with 6-dimethylaminopurine produced relatively small sized particles (2 nm) having a narrow size distribution. These particles did not exhibit any Ostwald's ripening and its solid sample could be fully redispersed in aqueous medium. Thermolysis results in the growth of these particles but demonstrates a better photocatalytic activity. Relaxation kinetics reveals the surface to contain a large number of surface states and the emission is originated by the presence of sulfur vacancies on the particle. The addition of indole simply quenches the emission of CdS in a bimolecular collisional process at a diffusion-controlled rate of about 9×109dm3mol−1s−1. Irradiation of the reaction mixture containing CdS and indole by light of λ>360 nm results in the formation of indigo with a quantum efficiency of 0.1.